(untitled) (Estudios de Historia de España, 2021)
The development of ethnic associations, which started in mid-1850 on Argentina, must address many conflicts that belong to the migrant’s daily life and the political context at the time, which he wants to solve. Amongst them, die away from home. The present investigation essay studies the confected proceedings in the Spanish Association of Mutual Aids from Rosario (AESMR) throughout almost three decades (1857-1885) focusing on the citations and representations of death in that collective and what were the strategies that they acquired in order to achieve a memory space for their fallen associates.